Auditory temporal resolution remains intact in low-frequency hearing loss: A case study - Andrew Stuart (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Objective: To explore the hypothesis that a low-frequency hearing loss would not signifi cantly impair an individual's auditory temporal resolution performance. Background: Listeners with high-frequency sensorineural hearing loss demonstrate poorer temporal resolution performance. This detriment has been attributed to the absence of high-frequency hearing. It is believed that functional hearing in these individuals is restricted to low-frequency auditory channels where temporal resolution, albeit normal, is characteristically poorer to that of the high-frequency channels. From this, one could hypothesize that a low-frequency hearing loss would not impair an individual's temporal resolution if high-frequency auditory channels remain intact.